2015
DOI: 10.1186/1752-1947-9-9
|View full text |Cite
|
Sign up to set email alerts
|

Giant anal condyloma (giant condyloma acuminatum of anus) after allogeneic bone marrow transplantation associated with human papillomavirus: a case report

Abstract: IntroductionCondyloma acuminatum are caused by human papillomavirus. Giant condyloma acuminatum is a locally invasive, destructive, and large sized mass. Risk factors for the development of giant condyloma acuminatum include an immunodeficient state, such as human immunodeficiency virus infection, post-organ transplantation, or post-allogeneic bone marrow transplantation. However, reports of giant condyloma after bone marrow transplantation are extremely rare (0.3 to 1.3%). The standard treatment for giant con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…While high risk types tend to cause anogenital malignant tumors, such as cervical, vulvar, vaginal, anal and penile cancers, where HPV types 16 and 18 are often found in high-grade dysplasia and malignancy. 1,17,18 Cervical cancer is one of the most common types of cancer in women which it is associated with HPV infection. Patients infected with HPV genotypes 6 or 11 had an increased risk of having CA (OR=2.34; 95%CI= 0.955-5.737; p=0.06).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While high risk types tend to cause anogenital malignant tumors, such as cervical, vulvar, vaginal, anal and penile cancers, where HPV types 16 and 18 are often found in high-grade dysplasia and malignancy. 1,17,18 Cervical cancer is one of the most common types of cancer in women which it is associated with HPV infection. Patients infected with HPV genotypes 6 or 11 had an increased risk of having CA (OR=2.34; 95%CI= 0.955-5.737; p=0.06).…”
Section: Discussionmentioning
confidence: 99%
“…Whereas, HPV types 16 and 18 are often found in highgrade dysplasia and malignancies. 1,17,18 A study conducted on high-risk women in Lagos showed a high prevalence of highrisk HPV types with most having one type of HPV. Age at first sexual intercourse and an increase in the number of sexual partners are the most important factors for high-risk genital HPV infection in this study.…”
Section: Introductionmentioning
confidence: 99%
“…Because Amyand’s hernias are typically incidental findings during surgical repair, the surgeon must be prepared to individualize treatment accordingly. Indeed, there have been reports of Amyand’s hernias ranging from the entrapment of a simple non-inflamed appendix to a hernia sac containing acute appendicitis with the simultaneous presence of a ruptured cecal adenocarcinoma; the former requiring simple reduction and possible appendectomy depending on surgeon preference and the latter requiring an emergent right hemicolectomy [ 18 ]. Though there is a growing collection of literature on Amyand’s hernias, the coexistence of acute appendicitis and a perforated cecum in the hernia sac is not well documented and to the authors’ knowledge this is one of the only instances of such an occurrence followed by an ileocecectomy and Bassini repair that has been reported.…”
Section: Discussionmentioning
confidence: 99%
“…In 2013, an investigation conducted in Turkey analysed 106 patients with CC found a prevalence of anal infection in 51.1% of all the cases of HR HPV (Guler et al, 2013). Lastly, a 2015 study conducted in Korea reported an extremely rare case of anal Giant Condylomata Acuminatum caused by HPV 6 (Hyun et al, 2015). Hidalgo and others demonstrated in 2018 that women who live with HIV have a higher prevalence and incidence of anal precursor lesions (high-grade squamous intraepithelial lesions) than cervical lesions.…”
Section: Hpv and Its Association With Digestive Tract Cancersmentioning
confidence: 99%